Analysis of Student Career Maturity Level Through Individualized Counseling with Techniques Client Centered - Nur Afifah Nabila Saragih; Rezki Hariko; Afdal Afdal (Universitas PGRI SUMATERA BARAT, 2023)
At the fulfillment stage of development, everyone will imagine choices, especially in terms of career development. A person must be capable and mature in determining future career choices. However, not everyone is able to face these problems, therefore help is needed, one of which is the help of counselor at school. This research aims to analyze student career maturity through individual client-centered technical counseling. This type of research is qualitative research using descriptive analysis methods. Data obtained from observation, interviews. This research was carried out at High School 10 Medan. The research subjects were 1 (one) counselor and 2 students who had career maturity problems and had implemented individual counseling selected based on the characteristics of the research focus. In this case, the counselor plays the role of implementing counseling. Students were selected based on recommendations from counselor because these students had the same problems as those being studied by researchers. The results obtained show that the student's maturity level has increased compared to before after being given individual counseling using client centered techniques by the guidance counselor.